The Assessment of material resource and cycle (MRC) of architectural finishing works for tall building construction. Issue 1 (1st December 2022) - Hajji, A M; Yulistyorini, A; Dewi, C P; Ahmad, M H
Abstract: This study is conducted to identify the application of GREENSHIP-based material resources and cycle (MRC) as part of green campus development in Universitas Negeri Malang (UM). The study focuses on the new two integrated classroom buildings in UM, which has nine floors with 44, 917 m 2 of total floor area. The parameters used in this study covers purchasing policy, waste management policy, the use of non-ODP refrigerant, existing conservation materials, and low environmental impact materials. The results of the study has shown that: (1) the prerequisite criteria for materials purchasing policies were fulfilled based on the use of environmentally friendly material categories in the building procurement process; (2) as for the waste treatment policy, there is the existence of a policy statement letter from the top management for waste processing and product saving campaigns; (3) the use of refrigerant without ODP are declared to be in compliance with the use of refrigerant type R410a with ODP value = 0; (4) since the building construction project use entirely new materials, the GREENSHIP requirement for used materials are not fulfilled; (5) 82.5% of materials for architectural finishing works are environmental-friendly as assessed from the materials specification; (6) regarding waste treatment practices, there is a separate waste processing facility for organic, inorganic and B3 type of waste as required by GREENSHIP.